A Sequential Solution to the Public Goods Problem - Cremer, Jacques; Riordan, Michael H. (Econometrica, 1985)
[Much attention has been devoted recently to the problem of implementing an optimal provision of public goods with imperfect information about preferences. The literature studies mechanisms with individual agents directly revealing information about their preferences, and focuses on two types of truthful equilibria: dominant strategy and Bayesian-Nash. We introduce "Stackelberg" mechanisms with truth-telling a dominant strategy for all agents but the first. The first agent plays "before" the other maximizing his expected utility on the assumption that others will reveal their true preferences. We present sufficient conditions for the construction of Stacekelberg mechanisms which yield an efficient provision of public goods, balance the budget, and induce every participant to reveal their true preferences. These results strengthen and extend the known results of the Bayesian-Nash approach.]